Mechanisms of HDACs in cancer development - Zhang, Ying; Wang, Haotian; Zhan, Zhumei; Gan, Lin; Bai, Out (Frontiers in Immunology, 2025)
Histone deacetylases (HDACs) are a class of epigenetic regulators that play pivotal roles in key biological processes such as cell proliferation, differentiation, metabolism, and immune regulation. Based on this, HDAC inhibitors (HDACis), as novel epigenetic-targeted therapeutic agents, have demonstrated significant antitumor potential by inducing cell cycle arrest, activating apoptosis, and modulating the immune microenvironment. Current research is focused on developing highly selective HDAC isoform inhibitors and combination therapy strategies tailored to molecular subtypes, aiming to overcome off-target effects and resistance issues associated with traditional broad-spectrum inhibitors. This review systematically elaborates on the multidimensional regulatory networks of HDACs in tumor malignancy and assesses the clinical translation progress of next-generation HDACis and their prospects in precision medicine, providing a theoretical framework and strategic reference for the development of epigenetic-targeted antitumor drugs.